2018
DOI: 10.1016/j.msec.2018.05.076
|View full text |Cite
|
Sign up to set email alerts
|

A UV-cured nanofibrous membrane of vinylbenzylated gelatin-poly(ɛ-caprolactone) dimethacrylate co-network by scalable free surface electrospinning

Abstract: Electrospun nanofibrous membranes of natural polymers, such as gelatin, are fundamental in the design of regenerative devices. Crosslinking of electrospun fibres from gelatin is required to prevent dissolution in water, to retain the original nanofibre morphology after immersion in water, and to improve the thermal and mechanical properties, although this is still challenging to accomplish in a controlled fashion. In this study, we have investigated the scalable manufacture and structural stability in aqueous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 99 publications
(133 reference statements)
1
25
0
Order By: Relevance
“…It is well known that gelatin nanofibrous membrane tends to be rubber-like in the wet stage and rigid-brittle in the dry stage [65]. is was mainly attributed to the presence of the EMImBF 4 solution dispersed in the pores of nanofibrous membrane, thus weakening the interaction among neighboring fibers [66,67].…”
Section: Effect Of Emimbf 4 On Ges Ges-25 After Immersionmentioning
confidence: 99%
“…It is well known that gelatin nanofibrous membrane tends to be rubber-like in the wet stage and rigid-brittle in the dry stage [65]. is was mainly attributed to the presence of the EMImBF 4 solution dispersed in the pores of nanofibrous membrane, thus weakening the interaction among neighboring fibers [66,67].…”
Section: Effect Of Emimbf 4 On Ges Ges-25 After Immersionmentioning
confidence: 99%
“…FSE was utilised to overcome the production scale limitations of needle-based electrospinning [ 30 ] and created a highly porous nonwoven membrane constructed of nanoscale diameter fibres. More than 95% of pores in PCL3%-E had a diameter of 1–2 μm, such that MSCs and fibroblasts are unlikely to penetrate due to size exclusion as BM MSCs have a diameter of 12–21 μm [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our design strategy was to select a clinically approved biodegradable material, i.e., poly(ε-caprolactone) (PCL), given its extensive body of literature, prevalent use in existing medical devices, and an established safety and functionality understanding [ 25 , 26 , 27 , 28 ]. Then, to overcome the well-known production limitations of needle electrospinning [ 29 , 30 ] and enable scalable manufacturing consistent with industrial needs, free surface electrospinning (FSE) was employed to a membrane suitable for application in CSBDs. Together with the physical characterisation, functional testing of the membrane was carried out in vitro to assess the absorption and release of PL, MSCs interactions, as well as the barrier functionality to cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin nanofibers (like collagen) have been used in biomedical applications such as cosmetics, wound dressing, tissue engineering, surgical treatments, etc [34]. Gelatin nanofibers (having sufficient mechanical properties to be used in these applications as nanofibrous mats) have been electrospun for ultrathin nanofibers [34][35][36][37][38][39][40][41][42][43][44]. These authors also reported that the properties of these nanofibers can be tailored as per requirements by optimizing input parameters such as voltage, viscosity, distance between the spinneret and rotating drum collector, and flow rate.…”
Section: Introductionmentioning
confidence: 99%